Pengaruh Komitmen Manajemen, Lingkungan Birokrasi, dan Pengetahuan Peraturan terhadap Penyerapan Anggaran Terkait Pengadaan Barang/Jasa - Nindy Okniafita; Dian Fitria Handayani (Universitas Negeri Padang, 2022)
This study aims to determinate the effect of management commitment, bureaucratic environment, and the regulatory knowledge on budget absorption related to the procurement of goods/services in the government of Pariaman City. A sample of 88 respondents was determined by using a total sampling technique consisting of heads of fields or staff of the procurement department. Data were analyzed using multiple regression formulas with the help of the SPSS application. This study concludes that management commitment does not effect budget absorption related to goods/service procurement. Bureaucratic environment has a positive and significant effect on budget absorption related to the procurement of goods/services. Mean while, the regulatory knowledge has no effect on budget absorption related to the procurement of goods/services.